2008
DOI: 10.1155/2008/761821
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of Gastric Cancer Patients with Node-Negative Metastasis following Curative Resection: Outcomes of the Survival and Recurrence

Abstract: of gastric cancer patients with node-negative metastasis following curative resection: Outcomes of the survival and recurrence. Can J Gastroenterol 2008;22(10):835-839.BACKGROUND: The purpose of the present study was to provide valuable prognostic information on lymph node-negative gastric cancer patients following curative resection. METHODS: Data from 112 lymph node-negative gastric cancer patients who underwent curative resection were reviewed to identify the independent factors of overall survival and recu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 42 publications
1
36
0
3
Order By: Relevance
“…Other studies demonstrated that the prognosis of the patients was associated with the absolute number of positive lymph nodes when the lymph node sampling was sufficient (16 required by TNM, AJCC 7th edition); however, the metastatic lymph node ratio and log odds of positive lymph nodes may be used to better assess prognosis when lymph node sampling was inadequate (31,32). In addition to the status of lymph node metastasis, the factors affecting the prognosis of gastric cancer also included TNM stage, depth of tumor infiltration, vascular invasion and nerve invasion (33,34). Histological classification (34) and tumor size (35,36) may also be used to predict the prognosis of patients with advanced gastric carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies demonstrated that the prognosis of the patients was associated with the absolute number of positive lymph nodes when the lymph node sampling was sufficient (16 required by TNM, AJCC 7th edition); however, the metastatic lymph node ratio and log odds of positive lymph nodes may be used to better assess prognosis when lymph node sampling was inadequate (31,32). In addition to the status of lymph node metastasis, the factors affecting the prognosis of gastric cancer also included TNM stage, depth of tumor infiltration, vascular invasion and nerve invasion (33,34). Histological classification (34) and tumor size (35,36) may also be used to predict the prognosis of patients with advanced gastric carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of the factors associated with survival and recurrence of LN-negative GC patients following curative resection is important to choose appropriate candidates for sequentially essential adjuvant therapy [10]. Although several investigators have reported that the postoperative prognosis of LN-negative GC patients was significantly better than that of LN-positive GC patients, some researchers found that a minority of LN-negative GC patients developed recurrence and poor survival.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Lai et al reported that male gender, elevated gross type, and presence of lymph node metastasis are related to early recurrence of EGC [30]. Deng et al reported that limited lymphadenectomy, few dissected nodes, and serosal involvement are related to postoperative recurrence in lymph-node-negative gastric cancer patients [31]. The results of the present study are consistent with those of previous studies, since high TNM stage was found to be an independent factor for tumor recurrence.…”
Section: Discussionmentioning
confidence: 99%